Molecular Characterization, Nutritional and Insulin Regulation of Elovl6 in Rainbow Trout (Oncorhynchus mykiss) - Yongnan Li; Yuning Pang; Zengqi Zhao; Xiaojun Xiang; Kangsen Mai; Qinghui Ai (Biomolecules, 2020)
Elongation of very long-chain fatty acids protein 6 (Elovl6) is a crucial enzyme in the synthesis of endogenous fatty acids, which participates in the energy balance and metabolic diseases. The main objective of this study was to explore the molecular characterization of Elovl6 and the regulation of elovl6 expression in response to dietary fatty acids and insulin. In the present study, the ORF (open reading frame) of Elovl6 from rainbow trout was cloned and characterized, which showed a high identity (87%) with mammals and other teleost. The results of quantitative PCR showed that the transcriptional levels of elovl6 from rainbow trout that were fed diets containing soybean oil (enriched with 18:2n-6, linoleic acid (LA)) or linseed oil (enriched with 18:3n-3, α-linolenic acid (ALA)) were lower than those in the group that were fed diets containing fish oil (enriched with 20:5n-3, eicosapentaenoic acid (EPA) and 22:6n-3, docosahexaenoic acid (DHA)). Correspondingly, mRNA expression of elovl6 in hepatocytes treated with DHA was dramatically higher than that in LA and ALA groups. The transcriptional expression of elovl6 in hepatocytes treated with insulin was also significantly increased. Moreover, the dual luciferase assay showed the transcription factor CREB1 dramatically up-regulated the promoter activity of elovl6, while FOXO1 significantly down-regulated the elovl6 promoter activity in rainbow trout. The differences in transcriptional expression of crbe1 and foxo1 may contribute to the increase or decrease of elovl6 expression in rainbow trout in response to fatty acids or insulin. These findings revealed the molecular characterization of elovl6 and the regulation of elovl6 expression by CREB1 and FOXO1 in rainbow trout in response to dietary fatty acids or insulin.